Electrochemical laser induced breakdown spectroscopy for enhanced detection of Cd(II) without interference in rice on layer-by-layer assembly of graphene oxides. (20th October 2016) - Jiang, Tian-Jia; Guo, Zheng; Ma, Ming-Jun; Fang, Li; Yang, Meng; Li, Shan-Shan; Liu, Jin-Huai; Zhao, Nan-Jing; Huang, Xing-Jiu; Liu, Wen-Qing
Abstract: Rice is considered to be one of the dominant sources of exposure to Cd(II) for human being, thus monitoring the concentration of Cd(II) in rice is very important. The anti-interference ability for several current approaches (especially electrochemical method) is expected to be dramatically improved due to more extreme complicated conditions in real rice sample. Here, a methodology combined electrochemistry with laser-induced breakdown spectroscopy (EC-LIBS), as well as choice of negatively charged graphene oxides (GO(-)), was selected for the determination of trace Cd(II) in rice. In this method, the target Cd(II) was preconcentrated on the surface of GO(-) modified Ti plate in the form of Cd(0) by electrochemcial deposition, the succeeding elemental identification and quantification was achieved using LIBS. Electrochemcial deposition and the modification of GO(-) on electrode significantly increased the sensitivity of the Cd(II) analysis in rice utilized LIBS only (for the same mass of rice sample) by 3 orders of magnitude and a ppb-level limits of detection (LOD) was obtained. Good anti-interference ability was also achievable during the actual measurements, particularly when Cu(II) and Mn(II) co-existed. The combination of electrochemistry and LIBS techniques, as well as the presence of GO, made it very attractive for the purposes of Cd(II) sensing in standard and nonstandard conditions.